"TineB", "Zgodovinar_666" in "assange" - kaj o identiteti posameznika razkrivajo uporabniška imena - Vranjek Ošlak, Urška (Slovenščina 2.0, 2016)
The research of usernames in comments of online articles and on Twitter showed that users who comment online news tend to cover their identity more often than Twitter users. We assume that the reason for this is that online news commentators mostly express their opinion, which may differ from the point of view of the online news portal. Due to anonymity, the opinion can be intensified or even radicalized. Therefore, commentators wish to at least partially conceal their identity. On the other hand, Twitter users frequently reveal their identity in their username, namely by using their real name and/or surname since the main purpose of using Twitter is for private communication and entertainment. On Twitter, it is also possible to find individuals who conceal their identity in order to express their opinion; however, they are less frequent. In usernames, users of both CMC types frequently replace their real name and/or surname with words that relate to their personal features (location, religion, characteristics, activity, horoscope and age) or express their interests (celebrities, nature, trademarks, interests, technology and mathematics, events, food). In this way, their identity is indeed obscure to some extent; however, they still express something about themselves. Users largely cover their identity by choosing an innovative username; they may use a general or neutral word or even construct their username in such way to make it difficult to determine its motivation. The analysis of the collected usernames also revealed some other username characteristics typical for online communication in general. In their usernames, users often play with language because they want the username to be innovative and unique in order to represent them online. Modifications of the text are frequent, i.e. switching letters or replacing them with numbers. Omitting diacritical signs (carons) on č, š, ž is also particular as such letters are often substituted by c, s, z or by letter combinations. Numbers may be used only as indexes or they may indicate the user%s age or year of birth or even refer to a number known from popular culture. Username specific are also the ways of marking word boundaries % words are most often separated by using upper- or lowercase and underscores. Usernames are predominantly written in lowercase.
Keywords: uporabniška imena; vzdevki; Twitter (družabno omrežje); komentarji; računalniško posredovana komunikacija